Concepts, History, Principles, and Application of Germplasm Cryopreservation Technology - Huiping Yang; Terrence R. Tiersch (EDIS)
Germplasm are living genetic resources that can serve as bearers of heredity, and include germ cells and their precursors, plant seeds and pollen, animal sperm, oocytes, embryos, and larvae. Cryopreservation refers to the preservation of biological materials at extremely low temperatures, typically using solid carbon dioxide at -80°C or liquid nitrogen at -196°C for freezing, and cryogenic storage in perpetuity. Germplasm cryopreservation is an important technology applied for medical treatment, maintenance of biological diversity, preservation of valuable genetic resources, assistance of breeding programs, and conservation of imperiled species. This extension publication is intended to introduce the basic concepts, history, principles, and applications of germplasm cryopreservation technology.